TECHNOLOGY FOR PRODUCING STABILIZING ETHER OF DRILLING MIXTURES POLYPATS FOR THE OIL AND GAS INDUSTRY BASED ON FIBROUS WASTE FROM POLYESTER PRODUCTION - Asadova Rano Dilmuratovna; Murodov Muzaffar Murodovich; Kuziev Khusniddin Zhuraevich (Web of Journals Publishing, 2025)
At present, the production of organic substances and materials based on them, reagents of composite composition based on the processing of separated waste by mechanochemical and other methods is one of the most important tasks. This, in turn, exerts its influence with radical changes on the equipment of production of existing industrial enterprises, i.e. on the principles of constant technological sequence - step by step loads the tasks of reconstruction and modernization at the enterprise. According to the illuminated world experiences and subsequent results, one of the important problems is their large-scale implementation in production and the creation of innovative start-up technologies for obtaining composite polymers based on waste from manufacturing enterprises of polyester fibers used for the production of household and hygienic products, as well as textiles from natural fibers, carpets and carpet products.
Keywords: Polyester fibers, polyethylene terephthalate, lavsan, trilene, inhibitor, reagents, drilling mud, well, cellulose, polyanionic cellulose, carboxymethyl cellulose, degree of polymerization.